Positive psychology : the basics - Hart, Rona (Abingdon, Oxon ; New York, NY : Routledge, 2020)
This book provides an accessible and balanced introduction to positive psychology scholarship and its applications, incorporating an overview of the development of positive psychology. Positive Psychology: The Basics delineates positive psychology's journey as a discipline, takes stock of its achievements and provides an updated overview of its core topics, exploring the theory, research and interventions in each. Launched as a rebellious discipline just over two decades ago, positive psychology challenged the emphasis of applied psychology on disease and dysfunction and offered a new, more balanced perspective on human life. From its foundations in the late 20th century to recent "second-wave" theories around the importance of recognizing negative emotions, this compact overview covers the key ideas and principles, from research around emotional wellbeing, optimism and change, to posttraumatic growth and positive relationships. The first jargon-free introduction to the subject, Hart introduces the reader to a range of issues, including self-regulation and flow, character strengths and virtues and positive relationships, concluding with a chapter on how interventions can affect happiness and wellbeing. Positive Psychology: The Basics is an essential resource for students, practitioners, academics and anyone who is interested in understanding the essence of a life well lived.
OCLC-licensed vendor bibliographic record.
Keywords: Positive psychology; PSYCHOLOGY / General; PSYCHOLOGY / Applied Psychology